Historia, historiografia a wiarygodność historyczna. Księga Kronik na tle starożytnego piśmiennictwa bliskowschodniego i grecko-rzymskiego - Kalimi, Isaac (Wydział Teologiczny UAM, 2009)
The purpose of this article is to express, expand and sharpen views concerning history, historiography, historical evaluation and reliability, and the main literary nature of the book of Chronicles as a whole in its own historical context. These are vital issues that have direct implications for understanding the book, its content, its purpose, and credibility as a source for the history of Israel in the monarchic period, and for the development of Judaism in the Second Temple era. In order to accomplish this task, some common features of the Chronicler’s writing and the related ancient Near Eastern and Greco-Roman historical writings are provided. Furthermore, the presumed Chronicler’s lines of thought and his evaluations of sources are scrutinized and exemplified, and the historical trustworthiness of some details, which appear only in Chronicles, is examined in order to demonstrate that the book contains some potential reliable data.
History, Historiography and Historical Credibility in Chronicles Compared to the Ancient Near Eastern and Greco-Roman Cultures
Keywords: Chronicles; historiography; dialectic between the present and the past; reliability